Digital Marketing In India, Its Trends And Future Growth (Trinity Journal of Management, IT & Media (TJMITM), 2016)
With the tremendous and broadly scattered populace of India it  has dependably been a test for organizations to control market  progress and they need to strive to make their vicinity felt all  through the length and expansiveness of the country. Gone are the  days when an insignificant promotion on radio or an imaginative  publicizing battle was sufficient to hypnotize the objective client.  Today digital consumer is articulate and demanding driving  global conversations on every product and service influencing  brand image and bottom line like never before. a comprehensive  digital marketing solution that helps engage with consumer,  influence their opinions, provide relevant feedback, reach various  demographics and glean actionable insights- thus become critical  to successful corporate strategy. The developing web entrance, the  high offers of advanced mobile phones and the 3G administrations  being generally made accessible by cell telephone organizations  in India together make impeccable conditions for a computerized  upset to occur. What’s more, this is going on the grounds that if in  today’s age an organization or brand “is out of site it goes out of  psyche”, consequently promoting has turned into a fundamental  malice. The advertising arrangement essentially means to make  the business furnish the arrangement with the mindfulness with  the normal clients. From 1980 onward, on the other hand, the  Indian state has moved Indian political economy towards East  Asian models of improvement. This paper aims to know the scope  of digital marketing in India, its trends and future growth.
Keywords: Digital Marketing; objective client; digital consumer; mindfulness; political economy